O arroz orgânico como estratégia de produção e reprodução social: o caso do assentamento filhos de Sepé, Viamão/RS - Beling, Helena Maria (2017)
The present research deals with a study on the production of organic rice in settlement Filhos de Sepé, located in the municipality of Viamão/RS, which is a production based on the principles of Agroecology. In the context of changes that include land reform and environmental crisis, arising from the intensive use of pesticides in rice production, this research aims to answer the following questioning: how farmers of the settlement Filhos de Sepé, located in the municipality of Viamão/RS, if organize the production of organic rice, starting on the agroecological transition and the maintenance of this production system, as well as the social and productive organization that settlement. To answer the problem of the research, it was established as a general objective: to understand the agroecological conversion process and the maintenance of the organic rice production system in the settlement of Filhos de Sepé, Viamão/RS. More specifically it his intended: characterize the challenges and motivations of settlers of settlement Filhos de Sepé in organic rice production; understand the social, cultural, economic and environmental setting of the producers of organic rice in settlement Filhos de Sepé; identify the types of certification of organic rice in the settlement Filhos de Sepé. To achieve the objectives proposed in the research was selected approach and qualitative analysis. The method to be used is dialectical, because, it is what is closest to the reality of research. Because of the need to gather information on the study area, this paper presents the methodological procedures divided into three phases. The first phase consisted of the initial and the guidelines, survey and analysis of bibliographic material, which are the secondary data, it will be the basis for the construction of the theoretical framework of the research. The second phase will be the primary data collection conducted through field work, together with the settlers and technicians of settlement Filhos de Sepé; and in the first instance, it performed the recognition and characterization of the settlement Filhos de Sepé, taking into account the cultural, social, economic and physiographic, after, was carried out data collection with relatives settled and technicians settlement with implementation of the roadmap of semi-structured interviews, informal conversations, systematic observation and nonparticipant observation. The third phase consists of the intersection of data and information collected, enabling specific analysis of the study area. In this harvest(2015/2016), the organic rice production area in the settlement was 1,600 hectares, involving 157 families, organized in to 25 production groups. In the production of organic rice, the settlement is one of the largest producers in the country and the largest in the state. Organic certification in the settlement is carried out in two ways, namely: through audit, performed by the certifying company IMO and participatory certification, performed by the Sistema Participativo de Garantia.